2018
DOI: 10.1021/acs.biochem.8b00635
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Insulin-Like Growth Factor-Binding Protein 3 With Hyaluronan and Its Regulation by Humanin and CD44

Abstract: Insulin-like growth factor-binding protein-3 (IGFBP-3) belongs to a family of IGF-binding proteins. Humanin is a peptide known to bind residues 215-232 of mature IGFBP-3 in the C-terminal region of the protein. This region of IGFBP-3 was shown earlier to bind certain glycosaminoglycans including hyaluronan (HA). Here, we characterized the binding affinities of the IGFBP-3 protein and peptide (-KKGFYKKKQCRPSKGRKR-) to HA and to humanin and found that HA binds with a weaker affinity to this region than does huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
69
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 17 publications
(86 citation statements)
references
References 68 publications
8
69
1
Order By: Relevance
“…Only a small effect was observed upon adding the IGFBP-3 protein alone or in combination with the antibody, 5F12, or 4-MU treatment. In accord with our previous results 51 , we found that blocking HA-CD44 interactions in A549 cells with 5F12 reduced cell viability to the same extent as that found by the addition of only IGFBP-3 ( Fig. 3B).…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Only a small effect was observed upon adding the IGFBP-3 protein alone or in combination with the antibody, 5F12, or 4-MU treatment. In accord with our previous results 51 , we found that blocking HA-CD44 interactions in A549 cells with 5F12 reduced cell viability to the same extent as that found by the addition of only IGFBP-3 ( Fig. 3B).…”
Section: Resultssupporting
confidence: 93%
“…We previously showed that the IGFBP-3 peptide exhibits similar binding affinities to HA as the full-length protein 51 . The results here show that the IGFBP-3 peptide is better able to bind HA than either IGFBP-5 or −6 peptides ( Fig.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations